2019
DOI: 10.1002/humu.23734
|View full text |Cite
|
Sign up to set email alerts
|

NBAS pathogenic variants: Defining the associated clinical and facial phenotype and genotype–phenotype correlations

Abstract: The pathogenic variants in the neuroblastoma‐amplified sequence (NBAS) are associated with a clinical spectrum involving the hepatic, skeletal, ocular, and immune systems. Here, we report on two unrelated subjects with a complex phenotype solved by whole‐exome sequencing, who shared a synonymous change in NBAS that was documented to affect the transcript processing and co‐occurring with a truncating change. Starting from these two cases, we systematically assessed the clinical information available for all sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Progressive reduction in NK cells numbers has been described by Garcia Segarra et al (15) and then by Ricci et al (10). As Figure 2 demonstrates, the patients who had immunodeficiency and bone disease had mutations distributed along the gene, with no particular domain predominance (10,(14)(15)(16)(17)(18)(19)(20)(21)(22)(27)(28)(29)(30)(31)(32)(33)(34)(35), current study).…”
Section: Literature Reviewsupporting
confidence: 72%
See 1 more Smart Citation
“…Progressive reduction in NK cells numbers has been described by Garcia Segarra et al (15) and then by Ricci et al (10). As Figure 2 demonstrates, the patients who had immunodeficiency and bone disease had mutations distributed along the gene, with no particular domain predominance (10,(14)(15)(16)(17)(18)(19)(20)(21)(22)(27)(28)(29)(30)(31)(32)(33)(34)(35), current study).…”
Section: Literature Reviewsupporting
confidence: 72%
“…This syndrome is characterized by autosomal recessive inheritance, severe postnatal growth impairment, facial dysmorphisms with senile face, small hands and feet, and normal intelligence. Subsequent case reports have described immunological defects in some patients with SOPH syndrome (10,(15)(16)(17)(18)(19)(20)(21)(22). Recent studies demonstrated SOPH syndrome to be only a part of a clinical spectrum ranging from isolated acute liver failure to a complicated phenotype that includes skeletal dysplasia, immunological abnormalities, and the involvement of other organs (10,16).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies of chromosomal anomalies have found predictable relationships between facial traits, such as nasal bridge and eyebrow shape or dental features, and microdeletions or translocations [9,24] Facial similarity and perception of selfresemblance in the present study is likely unrelated to genetic and chromosomal abnormalities. Therefore, the feasibility of finding a positive relationship between genes and facial features is supported by previous studies of phenotype and chromosomal anomalies.…”
Section: Discussionmentioning
confidence: 44%
“…NBAS mutations have also been identified in SOPH syndrome patients without liver failure [4]. An increasing number of studies have indicated that diseases based on NBAS mutations have a broad phenotypic spectrum, ranging from isolated recurrent ILFS2 to a multi-systemic disease manifesting as short stature, skeletal dysplasia, dysmorphism and optic atrophy with or without liver failure [4][5][6][7][8][9][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%